Neutron diffraction study of tetragonal zirconias containing Sn - Hunter, BA; Howard, CJ; Kim, DJ (ELSEVIER SCIENCE BV, 1997)
Neutron powder diffraction was used to study tetragonal (ZrO2 - 2 mol% Y2O3)-M mol% SnO2 at various Sn compositions, M = 0-10. It was confirmed that there is an increase in the unit cell volume even though the shortest cation-anion bond distance decreases as expected from the smaller ionic radius of Sn. This result is explained in terms of charge balance effects. (C) 1998 Elsevier Science B.V. All rights reserved.